2019
DOI: 10.7554/elife.43922
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic repression by BCL6 controls the genome-wide liver response to fasting and steatosis

Abstract: Transcription is tightly regulated to maintain energy homeostasis during periods of feeding or fasting, but the molecular factors that control these alternating gene programs are incompletely understood. Here, we find that the B cell lymphoma 6 (BCL6) repressor is enriched in the fed state and converges genome-wide with PPARα to potently suppress the induction of fasting transcription. Deletion of hepatocyte Bcl6 enhances lipid catabolism and ameliorates high-fat-diet-induced steatosis. In Ppara-null mice, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 67 publications
5
71
0
Order By: Relevance
“…A composite element of an NR and an LDTF is not unprecedented, as several steroid hormone receptors interact with Forkhead box (Fox) A1, and joint direct DNA binding by androgen receptor and FoxA1 has also been observed (37). Moreover, the other two PPAR family members interact with the non-NR protein BCL6 (38,39). The C/EBP:DR1 composite element not only enriched was but also showed elevated levels of both the C/EBP and PPAR␥ proteins, suggesting that the 5= extension can be bound from both the major and minor grooves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A composite element of an NR and an LDTF is not unprecedented, as several steroid hormone receptors interact with Forkhead box (Fox) A1, and joint direct DNA binding by androgen receptor and FoxA1 has also been observed (37). Moreover, the other two PPAR family members interact with the non-NR protein BCL6 (38,39). The C/EBP:DR1 composite element not only enriched was but also showed elevated levels of both the C/EBP and PPAR␥ proteins, suggesting that the 5= extension can be bound from both the major and minor grooves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified hepatocyte B-cell lymphoma 6 protein (BCL6) as a negative regulator of the PPARα-dependent transcription program during fasting. BCL6 interacts with a high number of the same genes as PPARα and represses lipid catabolism in the fed state [269]. Intriguingly, though PPARα is required for the adaptive response to fasting, it is dispensable during intermittent fasting, a condition that ameliorates hepatic steatosis [270].…”
Section: Ppars In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Recently, a study by Çalışkan et al () provided enhancer and promoter maps derived from a larger set of samples generating the most comprehensive map of active liver cis ‐regulatory elements to date (Figure ). Integration of such epigenomic datasets and subsequent TF binding motif analysis can enable identification of TFs that orchestrate liver‐specific cis ‐regulatory networks, along with their specific cistromes (Deplancke, Alpern, & Gardeux, ; Goldstein et al, ; Joo, Koo, Kim, Kim, & Kim, ; Sommars et al, ). Importantly, the gathering of these epigenomic datasets constitutes an important first step for prioritization and interpretation of liver disease‐associated genetic variants that may reside within noncoding regulatory sequences rather than in protein‐coding regions, a plausible scenario given the general enrichment of disease‐associated variants in accessible chromatin and TF motifs (Maurano et al, ; Quang, Erdos, Parker, & Collins, ).…”
Section: Liver Cis‐regulatory Networkmentioning
confidence: 99%
“…In order to maintain metabolic homeostasis, the liver transcriptional network is also required to be tightly regulated in the fed state. The B cell lymphoma 6 (BCL6) transcriptional repressor has been recently implicated in the active suppression of fasting transcriptional programs regulated by PPARα (Figure ), identifying over 50% of the liver transcripts affected by fasting as BCL6‐PPARα targets (Sommars et al, ). This study also highlighted an intricate relationship between fed‐fasting gene regulatory networks and NAFLD, as loss of hepatic Bcl6 enhanced lipid catabolism and reduced HFD‐induced steatosis (Sommars et al, ).…”
Section: Liver Enhancer Dynamicsmentioning
confidence: 99%